Korupsi dan Pengaruh Kekuasaan Partai Politik (Follow The Money and Asset Recovery) - Hartanto Hartanto; Edy Chrisjanto; Murdomo Murdomo (Iqtisad: Reconstruction of Justice and Welfare for Indonesia, 2024)
Corruption can be defined as an extraordinary crime. The consequences of corruption crimes can damage democratic values, morals (local wisdom), harm the country's finances and/or economy, and violate the social and economic rights of the community. Agencies responsible for investigating and prosecuting criminal acts of corruption include the police, prosecutor's office, and the Corruption Eradication Commission. Corruption is defined as the actions of those in positions of authority, including politicians and civil servants, who enrich themselves illegally and unfairly, abusing the power entrusted to them by society. Corruption is defined as the misappropriation of state or government funds (including those of companies, organizations, and foundations) for personal or other individuals' interests. It is imperative that law enforcement agencies prioritize focus, prevention, and strengthening. The research method employed is a legal and doctrinal approach, which examines secondary data. The author concludes that corruption persists and that the integrity of law enforcement officers is questionable. To eradicate corruption, it is necessary to re-focus on methods such as "follow the money" and "asset recovery." It is also essential to make legal breakthroughs regarding digital exposure or publication, and to implement prevention and control of criminal acts of corruption, including carrying out prevention and education efforts within political parties. Abstrak Korupsi dapat diakualifikasikan kejahatan luar biasa, akibat kejahatan korupsi dapat merusak nilai-nilai demokrasi, moral (kearifan lokal), merugikan keuangan dan/ perekonomian negara, melanggar hak-hak sosial dan ekonomi masyarakat. Instansi yang berkaitan dengan penuntutan tindak pidana korupsi, yaitu kepolisian, kejaksaan, dan Komisi Pemberantasan Korupsi. Korupsi diartikan sebagai tindakan penguasa, baik politisi (dalam keterkaitan tertentu) maupun pegawai negeri, yang memperkaya diri sendiri secara tidak sah dan/ tidak adil, menyalahgunakan kekuasaan yang dipercayakan masyarakat kepadanya. Korupsi adalah penyelewengan dana negara/pemerintah (perusahaan, organisasi, yayasan, dan lain-lain) untuk kepentingan pribadi atau orang lain. Perlunya fokus dan pencegahan dan penguatan dalam penegakan hukum. Metode penelitian yang digunakan adalah pendekatan undang-undang maupun doktrin, yang mengkaji dari data sekunder. Penulis menyimpulkan bahwa korupsi tetap terjadi dan diwarnai integritas para oknum penegak hukum yang diragukan, pelaksanaan metode pemberantasan korupsi memerlukan pemfokusan kembali (re-focussing) terutama follow the money dan asset recovery, perlu dilakukan terobosan hukum tentang pemaparan atau publikasi digital, dan secara periodik tentang pelaksanaan pencegahan dan penanggulangan tindak pidana korupsi, termasuk melakukan upaya pencegahan dan edukasi di dalam partai politik.